Wireless vertical displacement measurment during running using an accelerometer and a mobile phone - Eriksson, M.; Sturm, D.; Halvorsen, K. A.; Gullstrand, L. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to investigate in the usability of a wireless accelerometer linked to a mobile phone via Bluetooth radio for measuring vertical displacement in running athletes. Five experienced runners were monitored during lactate threshold testing at three to five different velocities. Accelerometer data was received, processed and stored on the phone to be compared to simultaneous position transducer (ground truth) recordings after data collection. A paired t-test and statistical analysis show no significant differences in the reliability of the recordings. While further investigations are encouraged, the accelerometer and algorithm (running in J2ME on the mobile phone) proof as a flexible, easy-to-use tool for out-of-the-lab monitoring and to provide real-time feedback for running technique experiments.